Comparison of design of removable partial denture with conventional technique and computer-aided system: Perbandingan pembuatan desain gigi tiruan sebagian lepas dengan teknik konvensional dan sistem computer-aided - Melisa (Makassar Dental Journal, 2022)
In the last few decades, digital dentistry based on computer-aided design and computer-aided manufacturing (CAD/CAM) has been increasingly discussed. The use of CAD/CAM for the manufacture of fixed dentures shows a high success rate. Currently, CAD/CAM for the manufacture of removable partial dentures (RPD) has also been used in several studies. Several studies have been conducted to determine the level of accuracy and suitability of the manufacture of RPD made conventionally and CAD/ CAM systems, but there are still differences in results. Therefore, in this literature review, it will be discussed the comparison of the accuracy and suitability of conventionally made RPD and CAD/CAM systems.